Austria w drodze do nowoczesności. Era Józefa II – najwybitniejszego reformatora dynastii Habsburgów - Kowalczyk, Rafał (Jednostka wobec globalnego wymiaru stosunków międzynarodowych, 2021)
This text presents the policy of Joseph II seeking to transform the Habsburg monarchy into a modern, centrally managed capitalist state. Józef II was aware of the situation in which Austria found itself at the beginning of the 18th century and the insufficient scale of Maria Teresa’s reforms. The Habsburg monarchy was a technologically backward state, with strong feudal agriculture, and customs barriers between individual state provinces. It had an outdated fiscal system and huge public debt. Joseph II took part in several stages. He raised public debt, limited expenses, and sealed the tax system. He expanded communications by connecting individual provinces with Treist, hoping to increase exports from the monarchy. At the same time, he sought to make the monarchy a single, centralized state. In 1775 he managed to create a customs territory (Lower and Upper Austria, Czech Republic, Moravia, Silesia, Styria, Carinthia, Slovakia), to which Galicia was added in 1784. In the west of the Habsburg monarchy, customs territory did not include Tyrol and Vorarlberg as well as Lombardy and the surrounding area of Austria belonging to Austria, in the Adriatic region of Dalmatia and Istria as well as Hungary and Transylvania. Increased relief and stimulated the development of the manufacture industry. He tried to increase the share of the manufacture industry in the most backward regions of the monarchy. It succeeded only in the most industrialized regions of the Czech Republic and the Austrian principality, where the population of cities reached 15%. The Habsburg monarchy needed several decades to return to the state of economy during Joseph II (before the war with the Ottoman Empire). The distance to the economic powers with which Joseph II tried to compete in the eighteenth century was no longer to be cleared up.